Electroactive naphthalimide and naphthalenediimide interlayers for inverted perovskite solar cells - Armadorou, Konstantina-Kalliopi; AlSabeh, Ghewa; Vezzosi, Andrea; Najafov, Murad; Nasturzio, Pietro; Zimmermann, Paul; Hinderhofer, Alexander; Kim, Jinhyun; Zheng, Likai; Caldara, Tiziano Agostino; Carnevali, Virginia; Slama, Vladislav; et al. (Royal Society of Chemistry (RSC), 2026)
Perovskite solar cells have garnered significant interest, yet their limited operational stability remains a major challenge. This is especially pronounced at the interface with charge transport layers. In inverted p–i–n perovskite solar cells, fullerene-based electron transport layers pose critical stability issues. This has stimulated the application of low-dimensional perovskite interlayers featuring alkylammonium-based organic spacers that template perovskite slabs to enhance operational stabilities. However, these materials are traditionally based on organic cations that are electronically insulating, limiting charge extraction and device performance. We demonstrate the capacity to access low-dimensional perovskites incorporating electron-accepting naphthalimide- and naphthalenediimide-based spacers and use the corresponding organic moieties to modify or replace fullerene electron-transport layers, forming an electroactive interface that serves charge-transport. This resulted in superior performance with power conversion efficiencies exceeding 20% and enhanced operational stability, highlighting the potential of electroactive interlayers for advancing inverted perovskite solar cells.